Características químicas de solo cultivado com soja e irrigado com água residuária da suinocultura - Caovilla, Franciele A.; Sampaio, Silvio C.; Smanhotto, Adriana [UNESP]; Nobrega, Lucia H. P.; de Queiroz, Manoel M. F.; Gomes, Benedito M. (Universidade Federal da Paraíba (UFPB) Ccsa, 2010)
In this work the distribution was evaluated "in situ" of phosphorus (P), organic matter (MO), potassium (K), calcium (Ca), magnesium (Mg), cation exchange capacity (CEC), aluminum (Al), sum of bases (S), base saturation (V) and pH of a soil cultivated with soybean and irrigated with swine wastewater in the 0, 25, 50 and 75% levels. The factorial scheme was constituted by the 20, 40 and 60 cm soil depths and four wastewater levels with five repetitions. The results showed that significant difference occurred only for P, K and CEC in the soil profile. However, in all parameters, the 60 cm soil depth showed that the concentrations levels are similar to before the aplication of treatments.
Chemical characteristics of the soil cultivated with soybean and irrigated with swine wastewater
Keywords: pollution; ions leaching; environmental